Correlation Between Serum Total Bilirubin Levels and Blood Pressure Variability in Patients With Hypertension. (22nd September 2021) - Wang, Jun; Xu, Ya-nan; Tang, Long; Zhang, Jing-shui; Li, Zhen; Shao, Ming-liang; Hu, Long; Wang, Xian-ping
Abstract: Background: To investigate the effect of serum total bilirubin levels on blood pressure and its variability in patients with hypertension. Methods: This study was a retrospective observational study. A total of 189 subjects were recruited from September 2019 to March 2020. All hypertensive patients were scheduled for ambulatory blood pressure and a 24-hour dynamic electrocardiography. Standard deviations of 24-hour systolic and diastolic blood pressure were used as blood pressure variability indicators. A multiple linear regression was used to analyze the relationship between total bilirubin serum levels and blood pressure variability in hypertensive patients. Results: All patients were divided into 3 groups according to tertile values of total bilirubin: low (≤12.2 µmol/l, n = 64), moderate (12.3–16.7 µmol/l, n = 64), and high (>16.8 µmol/l, n = 62) total bilirubin groups. Compared with low total bilirubin group, 24-hour mean systolic and diastolic blood pressure, 24-hour systolic blood pressure standard deviation, systolic blood pressure coefficient of variability, and 24-hour systolic blood pressure load were reduced in the moderate and high total bilirubin groups (all P < 0.05). Multiple linear regression analysis showed that female ( B = −1.408, P = 0.013), age ( B = 0.043, P = 0.035), diabetes ( B = 2.624, P < 0.001), and moderate and high bilirubin grouping ( B = −1.582, −3.079; both P < 0.05) were influencing factors of 24-hour systolic pressure standard deviation. Serum total bilirubin levels had no effect on the standard deviation of 24-hour diastolic blood pressure( P > 0.05). Conclusions: In hypertensive patients, the total bilirubin serum level is an influencing factor for 24-hour systolic blood pressure variability.